2019
DOI: 10.4257/oeco.2019.2304.25
|View full text |Cite
|
Sign up to set email alerts
|

Anuran Species Composition From Chaco and Cerrado Areas in Central Brazil

Abstract: Herein, we present an updated inventory and the variations of frog communities' composition from five areas of humid Chaco and Cerrado in municipality of Porto Murtinho, Mato Grosso do Sul state, Brazil. This municipality is located in an area with three ecoregions: Chaco, Cerrado and Pantanal. Through acoustic and visual nocturnal/diurnal and pitfall evaluations from a period of over five years, we recorded 31 species in the Cerrado and 29 species in the humid Chaco. About 90% of the species were previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Although Souza et al (2017) reported the presence of these species, some records have recently been questioned. Santos et al (2019) suggested removing the species Boana crepitans (Wied-Neuwied 1924), Scinax similis (Cochran, 1952), Adenomera martinezi (Bokermann 1956) and Leptodactylus gracilis (Duméril & Bibron 1840). Brusquetti et al (2014) , suggested the incorrect identification of Lepidobatrachus asper Budgett, 1899 as Lepidobatrachus laevis Budgett, 1899 for the state.…”
Section: Introductionmentioning
confidence: 99%
“…Although Souza et al (2017) reported the presence of these species, some records have recently been questioned. Santos et al (2019) suggested removing the species Boana crepitans (Wied-Neuwied 1924), Scinax similis (Cochran, 1952), Adenomera martinezi (Bokermann 1956) and Leptodactylus gracilis (Duméril & Bibron 1840). Brusquetti et al (2014) , suggested the incorrect identification of Lepidobatrachus asper Budgett, 1899 as Lepidobatrachus laevis Budgett, 1899 for the state.…”
Section: Introductionmentioning
confidence: 99%
“…Those knowledge gaps limit our understanding of the historical changes in anuran assemblages in the study area, but the recent rise in research in this region and the advance in anuran taxonomy are contributing to a better comprehension of anuran diversity and its threats across the different ecoregions (Souza et al, 2017). A recent study on the composition of anuran assemblages in areas representing the Chaco and Cerrado found similar assemblages to those recorded in previous surveys a decade before (Santos et al, 2019), which suggests that during this period, assemblage composition has been resistant to changes. The most comprehensive work on the historical declines of amphibians focuses on the Atlantic Forest and reports that more than 100 species underwent population declines throughout the last century (Toledo et al, 2023).…”
Section: Discussionmentioning
confidence: 75%